Skeptisme Uni Eropa terhadap Regulasi Domestik Indonesia dalam Rangka Ekspor-Impor Crude Palm Oil: Indonesia Sustainable Palm Oil - Felisita Damayanti; Shary Charlotte Henriette Pattipeilohy (Journal of International Relations Diponegoro, 2020)
Palm oil is one of the important products for Indonesia to increase foreign exchange. The European Union is one of Indonesia’s list countries for exporting crude palm oil (CPO). The relationship between Indonesia and The European Union began to be disrupted by the implementation of the Renewable Energy Directive where either companies or countries that will export biomass products to EU members must choose one of nineteen certifications as a guarantee for the product has followed well sustainable. To enter the European Union’s CPO market, exporting countries must be certified in Roundtable on Sustainable Palm Oil (RSPO). However, based order from the Ministry of Agriculture, Indonesia is obliged to use Indonesia Sustainable Palm Oil (ISPO). The debate is ISPO has not been recognized in the international market causes ISPO cannot penetrate the European market. This research will explain why the European Union is skeptical of ISPO regulation using a green theory perspective. In addition, this research is aimed at palm oil suppliers to realize how important palm oil certification is for better environmental sustainability. The results of this study indicate that ISPO as regulation has not been able to fulfill the four Ten Key Values concepts to create ‘green’ palm regulations.